Las ruinas arqueológicas de México: arenas donde se disputa el patrimonio - Torre, Renée de la (Ciencias sociales y religión, 2021)
This article discusses the origins of the current large ritual and spiritual practices that take place in the main archaeological sites of Mexico. Two case studies were chosen that show contrasts and common patterns regarding governmental heritage management and the tensions generated between the different actors and different logics and approaches involved: Teotihuacan, place of key events of cultural nationalism where the spirituality of Mexicanity and the esoteric converge, and Chichén Itzá, a site in the Mayan area where the global networks of spiritualities linked to the New Age and the circuits of neo-Mexicanity converge. Through interviews and bibliographic follow-up with spiritual leaders who have ritually innovated with their esoteric, new-Ager, Mexicanist (indianist), neo-Mexicanity and neo-paganist cultural projects, the different initiatives that defined the archaeological zones as sacred places of alternative spiritual networks are reconstructed. Special attention is paid to the way in which archaeological zones have become arenas of dispute over the meaning of heritage where different agents converge (INAH, UNESCO, tourist agencies, spiritual leaders of Mexicanity, indigenous people, guardians of local tradition and New Age gurus) who seek to redefine and manage their memory, identity, meaning and use.